Judul artikel: judul artikel - Saputra, Aditya Tri; Rizal, Bayu Thomi (Jurnal Porkes, 2025)
This study aims to analyze the effect of boi-boian games on improving students' basic manipulative movement skills. The research method uses a quasi-experimental design experiment. The research sample was 64 fourth-grade students of SD Islam Teladan Suci using a total sampling technique. The research instrument was a test and measurement of throwing and catching abilities, with criterion validity based on established standards. The results showed that there was a difference in the average throwing and catching scores of the control class 11.41 and the experimental class 27.47 with a difference of 16.06. In addition, the results of the statistical test showed a significance value (sig. 2-tailed) of 0.000, which was smaller than the significance level of 0.05, indicating a significant difference between the control class and the experimental class. These findings indicate that boi-boian games contribute to improving basic manipulative movement skills by improving students' throwing and catching. This study provides important implications for teachers and schools in designing effective game programs and improving the atmosphere of students' PJOK learning. Thus, the boi-boian game can be used as one of the traditional games to improve the quality of basic manipulative movement skills in learning.